2D MXene Nanomaterials for Versatile Biomedical Applications: Current Trends and Future Prospects. Issue 46 (29th July 2021) - Lu, Beibei; Zhu, Zhenye; Ma, Biyuan; Wang, Wei; Zhu, Rongshu; Zhang, Jiaheng
Abstract: Research on 2D nanomaterials is still in its early stages. Most studies have focused on elucidating the unique properties of the materials, whereas only few reports have described the biomedical applications of 2D nanomaterials. Recently, important questions about the interaction of 2D MXene nanomaterials with biological components have been raised. 2D MXenes are monolayer atomic nanosheets derived from MAX phase ceramics. As a new type of inorganic nanosystems, they are being widely used in biology and biomedicine. This review introduces the latest developments in 2D MXenes for the most advanced biomedical applications, including preparation and surface modification strategies, treatment modes, drug delivery, antibacterial activity, bioimaging, sensing, and biocompatibility. Besides, this review also discusses the current development trends and prospects of 2D inorganic nanosheets for further clinical applications. These emerging 2D inorganic MXenes will play an important role in next‐generation cancer treatments. Abstract : In this review, the exfoliated method and application of MXene are summarized, especially the ionic liquid exfoliation of MXene, which is a new green, nontoxic and safe method and has great application potential in the medical field, such as photothermal therapy, photodynamic therapy, drug delivery, bioimaging, and antibacterial activity. Therefore, MXene materials have prospects in the field of medicine.